2006
DOI: 10.1111/j.1471-4159.2006.03890.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SOCS3 inhibits astrogliogenesis and promotes maintenance of neural stem cells

Abstract: To investigate the effects of suppressors of cytokine signaling 3 (SOCS3) on neural stem cell fate, stem cells were infected with an adenoviral vector expressing SOCS3. Three days later, western blot analysis and immunocytochemical analysis revealed that the protein level of MAP2 and the number of MAP2-positive cells were significantly increased in SOCS3-transfected cells, whereas the protein level of GFAP and the number of GFAP-positive cells were significantly decreased. Furthermore, promoter assay revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 37 publications
(40 reference statements)
2
33
0
Order By: Relevance
“…D, MC3T3-E1 cells were infected with Adeno-X-DsRed2 or pLP-Ad-SOCS3. 48 h after infection, cells were cultured in Met/Cys-free medium for 2 h. Cells were then pulsed with Trans 35 S label in the absence (lanes 1 and 4) or presence (lanes 2-3 and 5-6) of LPS for 2 h, and chased for 5 h with complete medium. Cell lysates were immunoprecipitated by using anti-C/EBP␤ antibody and analyzed by SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D, MC3T3-E1 cells were infected with Adeno-X-DsRed2 or pLP-Ad-SOCS3. 48 h after infection, cells were cultured in Met/Cys-free medium for 2 h. Cells were then pulsed with Trans 35 S label in the absence (lanes 1 and 4) or presence (lanes 2-3 and 5-6) of LPS for 2 h, and chased for 5 h with complete medium. Cell lysates were immunoprecipitated by using anti-C/EBP␤ antibody and analyzed by SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%
“…Met/Cys-free DMEM (MP Biomedicals, Solon, OH) supplemented with 5% dialyzed fetal calf serum (Hyclone, South Logan, UT) was added, and the cells were incubated for 2 h at 37°C with 5% CO 2 . Subsequently, the cells were incubated for 2 h in medium containing 160 Ci/ml of trans 35 Slabel (MP Biomedicals, Solon, OH) in the presence or absence of 100 ng LPS/ml. Radiolabeled proteins were then chased for 5 h in fresh complete medium.…”
Section: Volume 285 • Number 48 • November 26 2010mentioning
confidence: 99%
“…In this way, Socs3 recruits the proteasome to the ligand-occupied receptor complex and triggers degradation of its components as well as inhibition of Jak2 phosphorylation (Krebs and Hilton, 2001). Relevance of Socs3 to proper tuning of astrogenic rates was demonstrated by adenoviral transduction of Socs3 to rat E15-17 striatal precursors, followed by exposition of these cells to Lif or Lif/Fgf2 (Cao et al, 2006). It was found that Socs3 downregulates the astroglial output elicited by cytokine stimulation, in as little as 1 day.…”
Section: Modulating Jak2 Phosporylationmentioning
confidence: 95%
“…This was associated to early upregulation of NSC markers and delayed increase of the percentage of microtubule associated protein 2-expressing (Map2 + ) elements originating from the culture. That reasonably reflected an inhibition of glial commitment of NSCs, which, even in the presence of gliogenic citokines, retain their identity and are consquently available for alternative histogenetic pathways (Cao et al, 2006).…”
Section: Modulating Jak2 Phosporylationmentioning
confidence: 99%
“…In cultured cortical precursors, CNTF, LIF and CT-1 all promote astrocyte formation through LIFRβ/gp130 activation [153][154][155]. Integral to this pathway is signalling via STAT3, as highlighted by the observation that STAT3 activation in neural stem cells induces glial differentiation, while its inhibition promotes a neuronal fate [156,157]. Also, in neuroepithelial cells, STAT3 activation promotes astrogliogenisis via LIF induced bone morphogenetic protein 2 expression [158].…”
Section: Jak/stat Signallingmentioning
confidence: 99%